2014
DOI: 10.2196/jmir.2909
|View full text |Cite
|
Sign up to set email alerts
|

How Accurate is Web-Based Self-Reported Height, Weight, and Body Mass Index in Young Adults?

Abstract: BackgroundWeb-based approaches are an effective and convenient medium to deliver eHealth interventions. However, few studies have attempted to evaluate the accuracy of online self-reported weight, and only one has assessed the accuracy of online self-reported height and body mass index (BMI).ObjectiveThis study aimed to validate online self-reported height, weight, and calculated BMI against objectively measured data in young Australian adults.MethodsParticipants aged 18-35 years were recruited via advertiseme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
168
4
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(198 citation statements)
references
References 20 publications
19
168
4
7
Order By: Relevance
“…However, the validity of internet-based, self-reported 331 anthropometric data is high (42) and has been confirmed in the present study (26) . We were not 332 able to include dairy products as a dietary recommendation in the present analyses due to so 333 few individuals meeting the recommendation.…”
supporting
confidence: 76%
“…However, the validity of internet-based, self-reported 331 anthropometric data is high (42) and has been confirmed in the present study (26) . We were not 332 able to include dairy products as a dietary recommendation in the present analyses due to so 333 few individuals meeting the recommendation.…”
supporting
confidence: 76%
“…However, although individuals generally underreport weight and overreport height, the correspondence between anthropometric and self-report measures tend to be high (generally above .94; e.g. [64,65] ) and it is unlikely that small inaccuracies in BMI would have dramatically impacted our correlational findings. Second, we have not measured students' level of daily physical activity or dietary intake.…”
Section: Research Searching the Link Between Sleep And Bmi Amongmentioning
confidence: 87%
“…[62,63] There are some proofs that sleep education programs and cognitive behavior interventions can improve sleep in college students. [65] The current study has restrictions that should be addressed. First the study was designed as an exploratory study depending on a reasonably limited evidence showing that continues disturbanceof sleep can produce increased body weights by altering metabolic function.…”
Section: Research Searching the Link Between Sleep And Bmi Amongmentioning
confidence: 99%
“…Although family members received extensive instructions regarding these measurements, this may still have caused measurement bias, in particular among children between 12 and 17 years old, who may still be growing. Based on the literature, individuals overestimate their self-reported height and underestimate their self-reported weight, 15,16 although Christian et al 17 showed that self-reported weight following bypass surgery was close to the measured weight. Furthermore, since we were interested in BMI change over time, measurement bias may not have influenced our results to a large extent.…”
Section: Discussionmentioning
confidence: 99%